2005
DOI: 10.1158/1078-0432.ccr-05-0650
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Study of ABT-751, a Novel Microtubule Inhibitor, in Patients with Refractory Hematologic Malignancies

Abstract: Purpose: ABT-751is anoral antimitotic agent that binds to the colchicine site on h-tubulin. A phase 1study was conducted to determine the maximum tolerated dose and toxicities of ABT-751in patients with advanced myelodysplastic syndrome and relapsed or refractory acute leukemias. Study Design: Thirty-two patients were treated: nine with 100 (n = 3), 125 (n = 3), or 150 mg/m 2 (n = 3) of ABT-751 given orally once daily for 7 days every 3 weeks and 23 with 75 (n = 3), 100 (n = 3), 125 (n = 5), 150 (n = 5), 175 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 55 publications
1
54
0
Order By: Relevance
“…No other cases of drug-related liver dysfunction were observed in the study. Other tubulin modulating agents have also shown clinical elevations in transaminases, e.g., paclitaxel (7) and the tubulin-targeting VDA, ABT-751 (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…No other cases of drug-related liver dysfunction were observed in the study. Other tubulin modulating agents have also shown clinical elevations in transaminases, e.g., paclitaxel (7) and the tubulin-targeting VDA, ABT-751 (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the structural similarity of ELR510444 to ABT-751, which has been shown to bind to the colchicine site on tubulin (Yee et al, 2005), we evaluated whether ELR510444 also binds to the colchicine site. An assay that takes advantage of the fact that colchicine binding to tubulin can be monitored fluorometrically was used (Bhattacharyya and Wolff, 1974).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Broad-spectrum preclinical activity results included activity against paclitaxel-and vincristineresistant tumors [6]. In addition, ABT-751 appears to work as a vascular disrupting agent (VDA) thereby reducing tumor blood flow to enhance the cytotoxic effect [7,8]. This action is pertinent for patients with CRPC since targeting tumor vasculature appears an attractive treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of docetaxel and ABT-751 therapy had at least additive activity in xenograft models including the androgeninsensitive PC-3 prostate cancer model [10]. In phase I trials, the dose-limiting toxicities (DLTs) observed with ABT-751 were peripheral neuropathy, ileus and fatigue [8,11,12]. The recommended single-agent phase II dose was 200 mg daily on a 21/28-day schedule and is currently being evaluated in a number of phase II trials.…”
Section: Introductionmentioning
confidence: 99%